The concept of climate justice - Tykhomyrova, Yevhenya B. (My University, 2021)
Analyzes climate change as a recent threat of the early 21st century. It presents an understanding of the concept of climate justice in the context of political discourse. The purpose of the study is to analyze the nature of climate justice and the protest forms of its implementation. To ensure climate justice, climate policy must embrace human rights, gender equality, intergenerational justice and cultural integrity. In particular, climate justice is treated everywhere by the problems of environmental democracy, climate activism, climate apartheid, climate skepticism. The author believes that climate change should be addressed not only as an environmental issue, but also as a climate justice issue focused on how the most vulnerable people are affected.
Keywords: climate activism; climate aparthe id; climate skepticism; climate injustice; climate justice; climate change